Recognation Of Indigeneous Legal Community For Indigeneous Forest - Dilla Pratiwi Puji Rahayu; Erika Puspitasari; Azwar Annas; Agus Pujianto (Faculty of Law, University of Mataram, 2019)
This study aims to determined and described the legal history of forest management in Indonesia. For this study, regulation of the forest will be analyzed in each period of Indonesia legal history, namely the early days of independence, the old order regim, the new order regim, and the reformation era. Method use in this study is normative study, by using statute approach and historical approach. Result of this study can be describe that the legal history of forest arrangement in Indonesia was dynamics, comprises: the control of state toward the land including the customary land/customary forest based on the the right of state to control as stipulated in the 1945 Constitution, and the recognition of the indigineous legal community toward their customary forest.